P137 Success rate and safety profile of IPC insertion in benign pleural effusions. (11th November 2022) - Abdullah, Q; Bikmalla, S; Haris, M
Abstract : Introduction: Indwelling pleural catheter (IPC) has proved to be effective in reducing the need for further pleural procedures and hospital admissions in patients with malignant pleural effusion but its role in benign pleural effusion (BPE) is not well known. Recent studies suggests that IPC has a role in a specific cohort of patients with BPE. Aim: To review the outcomes and safety profile of IPC in BPE which were refractory to medical management and required repeated pleural drainage. Methods: Retrospective review of consecutive patients who had IPC insertion for BPE between 2013 to 2021. Results: 24 IPC were inserted for BPE including 15 for Congestive cardiac failure (CCF), 5 for Hepatic hydrothorax (HH), 2 for chronic pleuritis and 1 each for renal disease and benign asbestos pleural effusion. Median age of patients was 79 years and 67% were male. 83% of the procedures were performed as outpatient. Patients had an average of 3 pleural procedures before IPC insertion. 10 out of the 24 patients achieved spontaneous pleurodesis (42%) and 7 of these achieving pleurodesis were patients with CCF; median time to pleurodesis was 98 days. All of the 5 patients with hepatic hydrothorax failed to achieve pleurodesis. Complications include 4 pleural infections, 3 of which required a further pleural procedure and antibiotics. 3 out of the 5 patients with hepatic hydrothorax developed pleural infection (60%). 3 patients had mild site infections requiring short course of oral antibiotics only and 2 patients had blocked IPC's. Conclusion: IPCs can be inserted in BPE not responding to the standard medical therapy to control pleural fluid accumulation. This will help to avoid repeated procedures particularly in CCF. Majority of the patients can be managed as oupatients. Further studies are required to assess the safety and efficacy of IPC insertion in patients with hepatic hydrpthorax.